Enhancing oncology patient care: nurses’ knowledge, attitudes, and perceived benefits of early palliative integration - a cross-sectional study - Mohammed F. Hayek; Bahaaeddin M. Hammad; Faeda A. Eqtait; Ahmad Ayed; Basma Salameh; Nizar B. Said; Rasha S. Abu Zaitoun; Shurouq G. Qadous (BMC Palliative Care)
Abstract Background Palliative care aims to improve quality of life for patients with end-stage illnesses by addressing physical, psychological, social and spiritual needs. Early referral to palliative care improves patient outcomes, quality of life and overall survival in a variety type of cancers. This study aimed to assess knowledge, attitudes and perceived benefits of early integration of palliative care among oncology nursing. Methods A descriptive cross-sectional study was conducted in public, private, and educational hospitals located in Palestine. Data were collected using paper based self-administered questionnaires from nurses working in hematology, general oncology, and bone marrow transplantation departments. Results Among of 128 nurses, the study revealed a moderate level of knowledge (3.64 ± 0.96), Positive attitude (3.59 ± 1.02) and moderately recognized the perceived benefits of early palliative care (3.57 ± 1.02). A statistically significant difference in nurses’ knowledge, attitudes and perceived benefits of early palliative care based on clinical experience. Pearson’s correlation showed a significant positive relationship between the total knowledge and attitudes score (r = 0.211, p < 0.001), as well as with perceived benefits total score (r = 0.567, p < 0.001). Moreover, there was a significant positive relationship between the total attitude score and perceived benefits score (r = 0.303, p < 0.001). Conclusions These findings suggest that enhancing knowledge and highlighting the benefits of early palliative care integration could foster more favorable attitudes among oncology nurses. investing in education and training to have all nurses prepared to provide high-quality palliative care results in better patient outcomes and less suffering. Patients with advanced cancer should be referred to the palliative care teams at an early stage of treatment in conjunction with their treatment in order to improve patient outcomes and quality of life.